Rapid detection of Mucorales based on recombinase polymerase amplification and real-time PCR - Xu, Rui; Li, Dingchen; Zhao, Jingya; Zhong, Hanying; Chen, Hong; Jia, Yajing; Chen, Fangyan; Han, Li (Frontiers in Microbiology, 2023)
Mucormycosis, an invasive fungal disease with severe consequences, poses a significant threat to immunocompromised individuals. However, the timely and accurate identification of Mucorales infection continues to present difficulties. In this study, novel detection techniques utilizing recombinase polymerase amplification (RPA) and quantitative real-time polymerase chain reaction (qPCR) were developed, specifically targeting the mitochondrial rnl gene, in order to address this challenge. The specificity of the RPA and qPCR assay was assessed by adding genomic DNAs extracted from 14 nontargeted strains, as well as human and mouse blood. No false-positive results were observed.Additionally, genomic DNAs from 13 species in five genera of order Mucorales were tested and yielded positive results in both methods. To further evaluate the sensitivity of the assays, DNAs from Rhizopus oryzae, Mucor racemosus, Absidia glauca, Rhizomucor miehei, and Cunninghamella bertholletiae were utilized, with concentrations ranging from 1 ng/μL to 1 fg/μL. The limit of detection (LoD) for the RPA assay was determined to be 1 pg, with the exception of Rhizomucor miehei which had a LoD of 1 ng. The LoD for the qPCR assay varied between 10 fg and 1 pg, depending on the specific species being tested. Sensitivity analysis conducted on simulated clinical samples revealed that the LoD for RPA and qPCR assays were capable of detecting DNA extracted from 10 3 and 10 1 colony forming units (CFU) conidia in 200 μL of blood and serum, respectively. Consequently, the real-time RPA and qPCR assays developed in this study exhibited favorable sensitivity and specificity for the diagnosis of mucormycosis.